Analysis of Archetypes in Speak Graphic Novel by Laurie Halse Anderson - Wiratman Wiratman; Fina Amalia Masri; Eva Solina Gultom (ELITE: Journal of English Language and Literature, 2024)
This research aims to show the archetypes that occur in the Speak Graphic Novel. The purpose of this research is to analyze the archetypes of the main characters in the oral graphic novel by Laurie Halse. This research applies Carl Gustaf Jung's archetype theory. This research uses descriptive qualitative research. Data collection was carried out through four steps: reading, recording, analyzing data, and identifying data. The results of this research show that the Speak Graphic Novel shows the existence of two personas, five animus, one shadow, and one self archetype, before reaching the self archetype Melinda experiences an individualization process, in this graphic novel individualization appears when Melinda neutralizes this. things that cause him to use a persona and have to face the shadow that appears by providing real resistance to Andy who has been pressuring and threatening him. Another thing that helped the individualization process was Melinda's decision to accept the fact that she had made a mistake and forgive herself. Based on the results above, it can be concluded that in this novel the archetype is shown in full, starting from the details of the cause of the archetype's emergence to the start of the individualization process as a form of Melinda's effort to control or eliminate the cause of the archetype's emergence, which in the end causes the main character to achieve a self-archetype.